ANALYSIS OF STABILITY IN THE PROCESS OF MILLING THIN-WALLED WORKPIECE - NONG ShengLong; GAO ShangHan; HUANG Yan (Jixie qiangdu)
In order to analyze the stability of the thin-walled milling system, a continuous beam model of spindle tool workpiece system is established, from which, the equivalent mass and stiffness are obtained from the end of cutter and workpiece, respectively. The influences of workpiece sizes on milling stability of the system are researched consequently. The results show that the cross sectional width and height of thin walled workpiece has non-negligible influences on the milling stability. Among them, the height has greater impact, for a small height value pulls down the critical cutting depth severely. With the increase of the cross sectional height of workpiece, critical milling depth improves obviously. It is also noted that as the first natural frequency of the workpiece is close to or even greater than that of the spindle-cutter system, the workpiece’ shape has not significant influence on the milling stability. These above results can provide a theoretical basis for the stability machining for thin-walled parts.